Biphenotypic Acute Leukemia versus Myeloid Antigen-Positive ALL: Clinical Relevance of WHO Criteria for Mixed Phenotype Acute Leukemia. (24th July 2018) - Hammond, William A.; Advani, Pooja; Ketterling, Rhett P.; Van Dyke, Daniel; Foran, James M.; Jiang, Liuyan
Abstract : Updated WHO criteria define mixed phenotype acute leukemia (MPAL) with more stringent diagnostic criteria than the formerly described entity biphenotypic acute leukemia (BAL). The changes in diagnostic criteria influence management by assigning weight to aberrantly expressed markers and minimizing expression of myeloid markers other than myeloperoxidase (MPO), potentially foregoing consolidative allogeneic transplant for an otherwise "favorable" lymphoid phenotypic leukemia. We present a case of MPO-negative, myeloid antigen-positive acute lymphoblastic leukemia who progressed with refractory phenotypic acute myeloid leukemia while receiving lymphoid-directed therapy and discuss concerns raised by the adoption of the new, more stringent diagnostic criteria for BAL.